Розробка компонентів інформаційної системи з підтримки бронювання помешкання - Масалітіна, К. О. (ХНУРЕ, 2023)
This report examines the implementation of information system components to support accommodation reservations. The system enables hotel and property owners to manage their relationships with their customers effectively. The development process involves building a server and client-side system that enables users to browse through different accommodation options, select their preferred choice, make a reservation, and receive confirmation